Athyrium aberrans (Athyriaceae), a new species of the lady ferns from southeastern Xizang, China, based on morphological and molecular evidence - Qiu, Yong-Ling; Zhang, Lin; Zhang, Li-Bing; Zhou, Xin-Mao; Zhang, Liang (Phytotaxa, 2022)
A new fern species, Athyrium aberrans (Athyriaceae), currently only known from southeastern Xizang, China is described. Morphologically, A. aberrans is superficially similar to A. falcatum in the habit and pinna shape, but the new species can easily be distinguished from the latter by having purplish petioles and rachises, a bulbil on the rachis below the lamina apex, and finely toothed pinna margins. A phylogenetic analysis based on five plastid markers demonstrates that A. aberrans is most closely related to but obviously distinct from A. epirachis.